The Effect of Different Dietary Sugars on the Development and Fecundity of Harmonia axyridis - Li, Yan; Wang, Shasha; Liu, Yongkang; Lu, Yuting; Zhou, Min; Wang, Su; Wang, Shigui (Frontiers in Physiology, 2020)
The aim of this study was to screen synergistic substances included in existing artificial feeds in order to improve the fertility and survival rate of Harmonia axyridis, an efficient pest predator. To this end, we analyzed the potential effects of glucose and trehalose on the growth, development, and reproduction of H. axyridis and evaluated the effect of three different artificial feeds on the energy stress of H. axyridis. The feeds contained fresh pork liver, honey, sucrose, vitamin C, and royal jelly. Diet 2 and Diet 3 contained glucose and trehalose, respectively. The results showed that the development and reproduction of H. axyridis were affected by the different artificial feedstuffs. The pre-oviposition of H. axyridis on Diet 1 was slower than that of insects on Diet 2 and Diet 3. Additionally, the spawning quantity and incubation rate of insects on Diet 2 and Diet 3 were significantly higher than of those on Diet 1. Finally, the larval developmental time of Diet 1 insects was significantly slower than that of Diet 2 and Diet 3 insects. These results indicate that the addition of an appropriate amount of glucose or trehalose may affect positively the growth, development, and reproduction of H. axyridis.